Creating English Environment at Elementary School in Barito Kuala, south Kalimantan - Murtiningsih, Tenny; Lisnawati, Ica (UrbanGreen Central Media, 2021)
Language is a habit. As a habit, language is used everyday . We can use language as spoken language, written language and even sign language. As one of international language, English has to master well. One of the effort to make it happen is having English environment. This community service wants to describe about English environment in elementary school. This community service was done at elementary in Batola, South Kalimantan. The participants were the teachers from two (2) elementary schools in Batola, South Kalimantan. The result of this community service, the teachers have known how to create English environment at their school and practice it well in their school’s community